Bilateral TMJ Involvement in Rheumatoid Arthritis. (2nd April 2014) - Ruparelia, Pritesh B.; Shah, Deep S.; Ruparelia, Kosha; Sutaria, Shreyansh P.; Pathak, Deep
Abstract : Rheumatoid arthritis (RA) is a systemic inflammatory, slowly progressive disease that results in cartilage and bone destruction. Temporomandibular joint (TMJ) involvement is not uncommon in RA, and it is present in about more than 50% of patients; however, TMJ is usually among the last joints to be involved and is associated with many varied clinical signs and symptoms. Hence, RA of TMJ presents to the dentist with great diagnostic challenges. This report presents a case of RA with bilateral TMJ involvement with its classical radiographic findings and review literature.